Educational paper: Progression in chronic kidney disease and prevention strategies - Schäfer, Betti; Wühl, Elke (European journal of pediatrics, 2012)
Chronic kidney disease (CKD) in children is a rare but devastating condition. Once a critical amount of nephron mass has been lost, progression of CKD is irreversible and results in end-stage renal disease (ESRD) and need of renal replacement therapy. The time course of childhood CKD is highly variable. While in children suffering from congenital anomalies of the kidneys and the urinary tract, progression of CKD in general is slow, in children with acquired glomerulopathies, disease progression can be accelerated resulting in ESRD within months. However, irrespective of the underlying kidney disease, hypertension and proteinuria are independent risk factors for progression. Thus, in order to prevent progression, the primary objective of treatment should always aim for efficient control of blood pressure and reduction of urinary protein excretion. Blockade of the renin-angiotensin-aldosterone system preserves kidney function not only by lowering blood pressure, but also by reducing proteinuria and exerting additional anti-proteinuric, anti-fibrotic, and anti-inflammatory effects. Besides, intensified blood pressure control, aiming for a target blood pressure below the 50th percentile, may exert additive renoprotective effects. Additionally, other modifiable risk factors, such as anemia, metabolic acidosis, dyslipidemia, and altered bone-mineral homeostasis may also contribute to CKD progression. In conclusion, beyond strict blood pressure control and reduction of urinary protein excretion, identification and treatment of both, renal disease-related and conventional risk factors are mandatory in children with CKD in order to prevent deterioration of kidney function.